Механізм частотно-незалежної електропровідності водних розчинів електролітів - Bulavin, L.A.; Alekseev, A.N.; Zabashta, Yu.F.; Tkachev, S.Yu. (Publishing house "Academperiodika", 2022)
It is shown that the dependence of the resistance of a cell filled with a NaCl aqueous solution on the ac frequency cannot be explained as a result of only polarization phenomena in the boundary region at the electrode–electrolyte interface. A physical mechanism is proposed, which explains the monotonous increase of the solution specific conductivity at frequencies below 104 Hz, and its constant value in the frequency interval of 104–105 Hz. The temperature dependences for the diffusion coefficients of Na+ and Cl– ions in NaCl aqueous solutions and for the dimension of an physically infinitesimal volume (a region, where the local equilibrium is established) in this electrolyte are calculated. The space-time hierarchies in the NaCl aqueous solution are analyzed, and a relationship between a connection of the ac period with certain time characteristics, on the one hand, and the frequency dependence of the specific conductivity in this electrolyte, on the other hand, is demonstrated.